Gambaran Efikasi Diri Pada Penyandang Disabilitas Daksa Usia Remaja - Alfia Zahri; Vera Imanti (Academic Journal of Psychology and Counseling, 2022)
The life of an adolescents who will come is largely determined by the efficacy that is in him, how much the individual believes in his abilities.This study aims to find out how self-efficacy is in adolescents with physical disabilities, the type of research used is a qualitative case study. The technique of determining the subject is purposive sampling. The subjects in this study were three adolescents with physical disabilities in the Sehati Sukoharjo and family members of the main subject as supporting subjects. Data collection techniques using interviews. The validity of the data using source triangulation.The results of this study provide an overview of self-efficacy in adolescents with physical disabilities at the Sukoharjo Sehati Difabel Association. At the level aspect (level) is indicated by action, determination, confidence in self-ability, trust from the environment. Aspects of strength (strength) are shown by optimistic thinking, role models, recognition from the environment, previous self-competence, and emotional management. The generality aspect is shown by increasing skills and levels, solution strategies, and self-development with references.